Clinical profile of patients with deep neck space infections: a review of 62 patients from a tertiary care hospital of North India - Verma, Rohit; Angral, Sumeet; Singh, Udeyana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Deep neck space infection (DNSI) is the infection of the potential spaces in the neck, specifically around the facial planes. Management of DNSI is traditionally by prompt surgical drainage of the abscess followed by antibiotics. In select cases, nonsurgical treatment using appropriate antibiotics may be employed. The objective of this study was to review the clinical profile of patients with DNSI. Methods: This was a retrospective chart review of 62 patients of DNSI managed at a tertiary care hospital of North India. Various parameters assessed in study included the demographical profile of the patients, symptomatology, possible aetiology, site distribution, bacteriology, the co-morbid conditions and treatment received. Results: Male preponderance was seen in this study with male:female ratio of 1.69:1. Swelling was the main complaint in majority of the patients (91.9%, 57 of 62 patients). The most common aetiology was odontogenic infection. Diabetes mellitus was seen in 25.8% (n=16) patients. Multiple space involvement was seen in majority of the patients with submandibular space being the most commonly involved site (43.5%). Most patients had negative pus cultures. The most common organism isolated was Staphylococcus aureus. All patients underwent surgical drainage. Conclusions: Odontogenic pathology is the most common cause related to DNSI. So extreme caution should be exercised by dentists in diabetic patients and in those with other immunocompromised status. Pus culture should be obtained before the start of antimicrobial therapy. If not diagnosed and treated in time, DNSI can turn out to be fatal.